How to analyse time series data using cointegration techniques / Nik Muhd Naziman Ab Rahman - Ab Rahman, Nik Muhd Naziman (Universiti Teknologi MARA Kedah, Sungai Petani, 2002)
This paper examines the methods and procedures that are employed in order to analyse time series data. Unit root tests (Augmented Dickey-Fuller and Phillips-Perron) are performed to investigate the order of integration of each variable that enters the model. Models containing non-stationary variables normally lead to problems of spurious regression whereby the obtained statistical results indicate significant relationships between the variables in the equation when in actual fact they are only evidence of contemporaneous correlations instead of true causal relations. Analysis of cointegration enables researchers to deal with models involving non-stationary variables.